A Surrogate Matrix-Based Approach Toward Multiplexed Quantitation of an sGC Stimulator and cGMP in Ocular Tissue and Plasma. (April 2021) - Lin, Kenneth; Cabral, Pablo; Ekpenyong, Oscar; Bader, Suzy El; Galvao, Joana; Kim, Yeonil; Lu, Sherry X.; Tam, Yu Tong; Bruder, Marc; Rearden, Paul; Shankaran, Harish; Beaumont, Maribel
A liquid chromatography–tandem mass spectrometry assay was developed and qualified for the multiplexed quantitation of a small molecule stimulator of soluble guanylate cyclase (sGC) and its target engagement biomarker, 3′, 5′-cyclic guanosine monophosphate (cGMP), in ocular tissues and plasma from a single surrogate matrix calibration curve. A surrogate matrix approach was used in this assay due to the limited quantities of blank ocular matrices in a discovery research setting. After optimization, the assay showed high accuracy, precision, and recovery as well as parallelism between the surrogate matrix and the biological matrices (rabbit plasma, vitreous, and retina–choroid). This assay provided pharmacokinetic and target engagement data after intravitreal administration of the sGC stimulator. The nitric oxide-sGC-cGMP pathway is a potential target to address glaucoma. Increasing sGC-mediated production of cGMP could improve aqueous humor outflow and ocular blood flow. The sGC stimulator showed dose-dependent exposure in rabbit vitreous, retina–choroid, and plasma. The cGMP exhibited a delayed yet sustained increase in vitreous humor but not retina–choroid. Multiplexed measurement of both pharmacokinetic and target engagement analytes reduced animal usage and provided improved context for interpreting PK and PD relationships.